Parents Role In The Children's Development Of Self-Esteem - Yahaya, Azizi; Yow, Kiaw Geok (2003)
Self-esteem is a positive or negative orientation toward oneself. There are two essential components of healthy self-esteem; the sense of personal worth and a sense of personal competence or efficacy. These two components of self-esteem develop over a period of time with multiple experiences. People who are motivated will have high esteem, and having it indicates positive self-regard, not egotism. Negative self-esteem is related to many personal and social concerns, such as school failure, depression, social anxiety, violence, substance abuse, and chronic welfare dependency. In general, the more positive your self-esteem, the more successful you will be at dealing with life. It is important for all parents and teachers to understand how their children’s self-esteem is created and developed as well as how it can be maintained. The development of self-esteem plays an important role in helping individuals to make adjustment about their self-worth and competence. The primary contributor to self-esteem changes according to the stages they are in. True self-worth is developed over a lifetime and most of us will experience many highs and lows as we journey through life. A parent’s role is to help children feel loved and to teach them the skills they need to feel capable when faced with life's many challenges. Whatever the ability of the child is, the parents or the teachers must know ways to communicate and thereby build the self-esteem in the child. To steer the thoughts of their children in the right path, parents have to train them to respect individuals and not be influenced by peers' pressure or the masses. Competence builds the ego, success begets success, being loved is to give love and you command the respect of others if you have the self-esteem!